Perencanaan Kebutuhan Distribusi Sekunder Perumahan RSS Manulai II - Evtaleny R. Mauboy; Wellem F. Galla (Universitas Syiah Kuala, 2012)
Planning of secondary distribution for residence is important that should consider the load, plan the distribution network, choose the conductor and determine the transformer capacity needed. In this planning, Manulai II Resident is counted as simple household that the transformer is divided into two different areas A and B. Twisted Cable NFA2X size 3x70mm; 3x35mm; 4x25mm; and 2x10mm are used. The research shows that losses and voltage drop are still in tolerance limit and the capacity needed for area A is 50 kVA and 25 kVA for area B.